A cost allocation problem analyzed as a partition function form game - Kruś, Lech (Instytut Badań Systemowych. Polska Akademia Nauk, 2008)
In the paper a cooperative game in partition function is proposed for the cost allocation problem. The game describes real situations in which payoff of any coalition does not only depend on the players in the coalition but also on the coalition structure of other players. Solution concepts are analyzed. It is shown that the core of the game in partition function form is equal to the core of an appropriately formulated game in characteristic function form. On the base of the theoretical results, the core, the stable sets and several nucleoli concepts can be derived and utilized for decision support.
18 pages ; 21 cm
Bibliography p. 17-18
Keywords: Systemy wspomagania decyzji; Decision support system; Alokacja kosztów; Cooperative game theory; Cost allocation; Partition function form game; Teoria gier koperacyjnych; Gra w postaci funkcji partycji